Hubungan tingkat kepercayaan diri dengan obesitas pada siswa-siswi SMA Negeri 7 Manado - Wahyuni, Firman; Opod, Hendri; David, Lydia (Universitas Sam Ratulangi, 2016)
Abstract: Self-confidence is a certain degree of suggestion that develops in a person, so that, he/she feels confident in doing something, and accepts oneself as what it is. One of the factors that can lowers a person's self confidence is the physical appearance. Thus, the tendency to be overweight or obese can be annoying and be a source of concern and lack of confidence over the years of adolescence; therefore, the teens will be vulnerable to a variety of psychological problems. This study aimed to obtain the relationship between level of confidence and obese students at SMA Negeri 7 Manado. This was a correlation study with a cross sectional design. Samples were 62 students obtained by using purposive sampling. The instrument of this study was the scale of confidence with reliability (Î±) = 0.736 based on the characteristics of self-confidence which consisted of believe in oneself, act independently in making decisions, and have a positive sense of self. The results showed that confidence levels in obese adolescents were as follows: high category in 45 students (73%), moderate category in 17 students (27%); no low category was found. The Pearson correlation test showed an r value = -0.083 and a p value = 0.519. Conclusion: There was a negative relationship between self-confidence and obesity, albeit, the level of correlation was weak and insignificant.Keywords: obesity, self confidenceÂ Abstrak: Kepercayaan diri adalah suatu tingkatan rasa sugesti tertentu yang berkembang dalam diri seseorang sehingga merasa yakin dalam berbuat sesuatu, dan menerima diri apa adanya. Salah satu faktor yang dapat menurunkan kepercayaan diri seseorang ialah masalah penampilan fisik. Adanya kecenderungan menjadi gemuk atau mengalami obesitas dapat mengganggu dan menjadi sumber keprihatinan dan kurangnya rasa percaya diri selama bertahun-tahun masa remaja sehingga remaja akan rentan terhadap berbagai masalah psikologik. Penelitian ini bertujuan untuk melihat hubungan tingkat kepercayaan diri pada siswa yang mengalami obesitas di SMA Negeri 7 Manado. Jenis penelitian ini korelasional dengan rancangan potong lintang. Jumlah responden sebanyak 62 orang diperoleh dengan teknik purposive sampling. Alat ukur yang dipakai ialah skala kepercayaan diri dengan reliabilitas (Î±) = 0,736 berdasarkan ciri kepercayaan diri yaitu: percaya pada kemampuan diri sendiri, bertindak mandiri dalam mengambil keputusan, dan memiliki rasa positif terhadap diri sendiri. Hasil penelitian menunjukkan tingkat kepercayaan diri pada remaja yang obes berada pada kategori tinggi sebanyak 45 orang (73%), kategori sedang sebanyak 17 orang (27%), sedangkan kategori rendah tidak ada. Hasil uji korelasi Pearson diperoleh r = -0,083 dan p = 0,519. Simpulan: Terdapat hubungan negatif antara kepercayaan diri dengan obesitas namun tingkat korelasinya lemah dan tidak signifikan. Kata kunci: obesitas, kepercayaaan diri